Climatic analysis of a passive cooling technology for the built environment in hot countries - Calautit, John Kaiser; Hughes, Ben Richard; Nasir, Diana S.N.M. (Elsevier, 2016)
The aim of this work was to determine the ventilation and cooling potential of a passive cooling windcatcher operating under hot climatic conditions by replicating the monthly wind velocity, wind direction, temperature and relative humidity (RH) observed in a hot-desert city. The city of Ras-Al-Khaimah (RAK), UAE was used as the location of the case-study and available climatic data was used as inlet boundary conditions for the numerical analysis. The study employed the CFD code FLUENT 14.5 with the standard k–ε model to conduct the steady-state RANS simulation. The windcatcher model was incorporated to a 3 × 3 × 3 m3 test room model, which was identical to the one used in the field test. Unlike most numerical simulation of windcatchers, the work will simulate wind flows found in sub-urban environment. The numerical model provided detailed analysis of the pressure, airflow and temperature distributions inside the windcatcher and test room model. Temperature and velocity profiles indicated an induced, cooler airflow inside the room; outside air was cooled from 38 °C to 26–28 °C, while the average induced airflow speed was 0.59 m/s (15% lower compared to a windcatcher w/out heat pipes). Field testing measurements were carried out in the Jazira Hamra area of RAK during the month of September. The test demonstrated the positive effect of the integration of heat pipes on the cooling performance but also highlighted several issues. The comparison between the measured and predicted supply temperatures were in good agreement, with an average error of 3.15%.